Assessment of Family Functioning and Eating Disorders – The Mediating Role of Self-Esteem - Kroplewski, Zdzisław; Szcześniak, Małgorzata; Furmańska, Joanna; Gójska, Anita (Frontiers in Psychology, 2019)
The aim of the study was to measure whether people at increased risk for eating disorders (EDs) and people without an increased risk of eating disorders differ from each other in the assessment of family functioning (FF) and self-esteem (SE) dimensions. Moreover, the correlations between FF, EDs, and SE were verified, looking for the mediating role of SE in the context of the FF and EDs. The research was conducted on the group of 160 people aged from 18 to 47 years, including 74 people at increased risk for EDs. We used: The Family APGAR (Adaptability, Partnership, Growth, Affection, and Resolve); The SCOFF Questionnaire; The Multidimensional Self-Esteem Inventory, MSEI. Analyses indicate that the compared groups differ significantly in terms of EDs, assessment of FF, and all components of SE, in such a way that people without an increased risk of EDs are characterized by a more positive assessment of FF and higher SE in all its dimensions. All SE dimensions, except defensive high self-esteem, are mediators in the relationship of FF with EDs. In therapeutic interactions, it is worth focusing on the SE dimensions, as they are one of the mediation elements in the relationship between the assessment of FF and EDs.